Perbandingan Hasil Bleaching dengan Menggunakan Aluminium Foil dan Tanpa Aluminium Foil pada Hasil Warna Rambut Copper Blonde - Annisa Mardiva; Tyas Asih Surya Mentari (YASIN, 2026)
Hair aesthetics is an important aspect of the modern cosmetics industry, particularly in the copper blonde coloring trend, which requires a high level of lightness through the bleaching process. Although bleaching techniques continue to develop, empirical studies that specifically compare the effectiveness of using aluminum foil and not using aluminum foil in producing optimal color quality remain limited. This study aimed to analyze the differences in hair bleaching results between the technique using aluminum foil and the technique without aluminum foil. This study used an experimental method with a quantitative descriptive approach and a pre-experimental posttest-only design, involving 6 women aged 15–45 years in Padang City who were selected through purposive sampling. Data were collected using an assessment instrument for the quality of bleaching results based on the level of lightness, color uniformity, and tone accuracy, and were then analyzed through the normality test, homogeneity test, and Independent Sample t-Test. The results showed that the data were normally distributed and homogeneous, and the t-test yielded a significance value of 0.000 (<0.05), indicating a significant difference between the two techniques. The mean score of bleaching results using aluminum foil was 3.87, higher than that without aluminum foil at 2.68, indicating that the aluminum foil technique produced a better level of lightness and color uniformity. Thus, the use of aluminum foil is more effective in improving the quality of hair bleaching results. These findings contribute to the development of hair coloring technique methodology and provide practical implications for hairstyling practitioners in selecting a more efficient application technique to achieve optimal coloring results. This study also opens opportunities for further research involving a broader sample and analyzing the impact of bleaching on hair structure.